Depression and rising incidents of suicide among undergraduates in Nigeria: A survey of Southeast - Emeka Michael, Onwuama; Emmanuel J., Ibuot,; Christian, Agbo,; Aloysius, Obiwulu, (International Journal of Psychosocial Rehabilitation, 2024)
Background:Depression, and suicide experiences are prevailing in Nigerian higherinstitutions of learning. The need to find out their primary causes necessitated this study.Aims/Objectives: The aims were to investigate the primary factors responsible fordepression; and the relationship between the depression and rising incidents of suicideamong undergraduates in Southeast Nigerian universities.Methods: A cross-sectional survey wherein structured questionnaire was used to generatedata in 10 public universities was adopted. From a population of 79,751 students, 398 wasadopted as sample using Guilford and Flruchter (1973) formula for estimating sample size,while tables, percentage and the Statistical Package for the Social Sciences (SPSS version20.0) tools were used to dataanalyse.Results: The results reveal among others that lack of appropriate transportation andaccommodation systems; financial brokenness, imposition of textbooks/hand-outs andcompulsory sorting, disruption of academic activities; congested academic activities, andincompetency/poor academic performance are the major causes of depression amongundergraduates. It further reveals that hopeless,examination failure and majordisappointments, which cause depression, lead to suicide among undergraduates in SoutheastNigeria.Conclusions: Depression is inevitable among undergraduates and has a significantrelationship with the rising incidents of suicide in tertiary institutions in the Southeast.